Facilitation of caribbean intra regional trade in fresh produce due to the presence of the Pink Hibiscus Mealybug (Maconellicoccus hirsutus) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
32 páginas.